2005
DOI: 10.1002/ar.b.20055
|View full text |Cite
|
Sign up to set email alerts
|

Surface bone histology of the occipital bone in humans and chimpanzees

Abstract: Human and chimpanzee occipital bones are thought to grow and develop in distinctly opposite bone remodeling patterns. Preliminary research examining growth-remodeling fields (GRFs) from the surfaces of the occipital bone in modern humans and chimpanzee indicates this may not be entirely correct. By using vinyl/resin-casting techniques, coupled with scanning electron and reflected-light microscopy, GRF profiles from a cross-sectional sample of humans and chimpanzees have documented the ongoing histological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
0
11
0
4
Order By: Relevance
“…The mendosal suture, thus, develops in the region of the posterolateral (mastoid) fontanelle (Nakahara et al, 2003). Mowbray (2005), using the mendosal suture as a landmark, has found that just inferior to this suture that large areas of resting resorption is observed on the superior aspect of the cerebellar fossa in man. This author also found that just inferior to the mendosal suture resting resorption occurs, but on the inferior aspect of the cerebellar fossa in Pan.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mendosal suture, thus, develops in the region of the posterolateral (mastoid) fontanelle (Nakahara et al, 2003). Mowbray (2005), using the mendosal suture as a landmark, has found that just inferior to this suture that large areas of resting resorption is observed on the superior aspect of the cerebellar fossa in man. This author also found that just inferior to the mendosal suture resting resorption occurs, but on the inferior aspect of the cerebellar fossa in Pan.…”
Section: Discussionmentioning
confidence: 98%
“…The occipital bone arises from six ossification centers (Lang, 1983;Mowbray, 2005). The interparietal portion develops from two centers.…”
Section: Discussionmentioning
confidence: 99%
“…En general, los estudios de paleohistología de superficies óseas se han centrado en alcanzar una mayor exactitud en el registro de los rasgos característicos de cada tipo de actividad celular. En este sentido, se ha evaluado la performance de distintas técnicas de preparación del material y de diversos instrumentos para la observación de superficies óseas en el reconocimiento de campos de modelado óseo (Bromage, 1984;Mowbray, 2005;Martinez-Maza et al, 2010). Sin embargo, es importante evaluar también la precisión con la que se obtienen los datos, para garantizar así la consistencia de las observaciones .…”
Section: Discussionunclassified
“…En base a descripciones establecidas en trabajos anteriores (Boyde, 1972;Bromage, 1984;Mowbray, 2005;Martinez-Maza et al, 2010), se identificaron tres tipos de superficies: 1) Formación ósea: producto de la actividad de los osteoblastos (Fig. 2a).…”
Section: Registro Paleohistológicounclassified
See 1 more Smart Citation